Recurrent ovarian dysgerminoma in pregnancy: a rare case of successful maternal and fetal outcome - Tinwani, Sneha B.; Thakare, Sarika S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Dysgerminoma is a rare malignant ovarian germ cell tumor that typically affects women younger than age 30 and is highly sensitive to chemotherapy. Its occurrence during pregnancy is uncommon and recurrence during an ongoing pregnancy is extremely rare. We report the case of a 24 years old gravida 3 para 2 woman, previously diagnosed with left ovarian dysgerminoma, who presented at 27 weeks of gestation with a recurrent left adnexal mass and splenomegaly. Imaging revealed a large, multilobulated, vascularized pelvic-abdominal mass displacing the gravid uterus, with laboratory results showing elevated tumor markers. After multidisciplinary evaluation, the pregnancy was managed conservatively until 34 weeks, when increasing maternal symptoms necessitated emergency caesarean section with staging laparotomy. A healthy infant was delivered and the mass was completely excised along with total abdominal hysterectomy and right salpingo-oophorectomy. Histopathological examination confirmed recurrent dysgerminoma and the patient was subsequently started on platinum-based chemotherapy. This case highlights the importance of individualized, multidisciplinary care and timely intervention in achieving favourable maternal and fetal outcomes in pregnancies complicated by recurrent ovarian malignancy.